Vedolizumab: Potential Mechanisms of Action for Reducing Pathological Inflammation in Inflammatory Bowel Diseases - Luzentales-Simpson, Matthew; Pang, Yvonne C. F.; Zhang, Ada; Sousa, James A.; Sly, Laura M. (Frontiers in Cell and Developmental Biology, 2021)
Inflammatory bowel diseases (IBD), encompassing ulcerative colitis and Crohn’s disease, is a group of disorders characterized by chronic, relapsing and remitting, or progressive inflammation along the gastrointestinal tract. IBD is accompanied by massive infiltration of circulating leukocytes into the intestinal mucosa. Leukocytes such as neutrophils, monocytes, and T cells are recruited to the affected site, exacerbating inflammation and causing tissue damage. Current treatments used to block inflammation in IBD include aminosalicylates, corticosteroids, immunosuppressants, and biologics. The first successful biologic which revolutionized IBD treatment targeted the pro-inflammatory cytokine, tumor necrosis factor alpha (TNFα). Infliximab, adalimumab and other anti-TNF antibodies neutralize TNFα, preventing interactions with its receptors and reducing the inflammatory response. However, up to 40% of people with IBD become unresponsive to anti-TNFα therapy. Thus, more recent biologics have been designed to block leukocyte trafficking to the inflamed intestine by targeting integrins and adhesins. For example, natalizumab targets the α4 chain of integrin heterodimers, α4β1 and α4β7, on leukocytes. However, binding of α4β1 is associated with increased risk for developing progressive multifocal leukoencephalopathy, an often fatal disease, and thus it is not used to treat IBD. To target leukocyte infiltration without this life-threatening complication, vedolizumab was developed. Vedolizumab specifically targets the α4β7 integrin and was approved to treat IBD based on the presumption that it would block T cell recruitment to the intestine. Though vedolizumab is an effective treatment for IBD, some studies suggest that it may not block T cell recruitment to the intestine and its mechanism(s) of action remain unclear. Vedolizumab may reduce inflammation by blocking recruitment of T cells, or pro-inflammatory monocytes and dendritic cells to the intestine, and/or vedolizumab may lead to changes in the programming of innate and acquired immune cells dampening down inflammation.